Receptivno in produktivno znanje tujega in drugega jezika - Stanič, Daša (Vestnik za tuje jezike, 2013)
The purpose of this paper is to analize the subsets and the tasks of the competition in Italian as a foreign and second language in 2013. We were particularly interested in the share of the subsets and in the balance of receptive and productive tasks in the exams as well as in each particular subset. With the analysis of the subsets, it was found that in some of the four exams the subsets were unevenly represented. With a more detailed analysis of the tasks regarding the balance of receptive and productive tasks it was discovered that at levels A1 and A2 the exams were appropriately balanced, whereas at levels B1 and B2 the balance was not so good. While there were as many as two-thirds of the tasks in the exam for the level B1, which is intended for students that do not come from a bilingual area, productive, there were such only half of the tasks in the exam for the level B2, intended for students living in the bilingual area. In addition, the subset communication consisted of almost exclusively receptive tasks. In the future, the shares of the sections and the balance of receptive and productive tasks will need some further consideration regarding two criteria: the students competing in the competition are the best students in Italian so the share of productive tasks should not fall below 50% and in addition, the difference between students coming from bilingual area and the others should be taken into account.
Keywords: Italian; italijanščina; tuji jeziki; tuji/drugi jezik; preverjanje znanja; receptivne naloge; produktivne naloge; tekmovanja